Tiny diatoms Minidiscus vodyanitskiyi sp. nov. (Bacillariophyta) from the Sea of Azov and consideration of polygonal areolae pattern - Lyakh, Anton M.; Bedoshvili, Yekaterina D. (Phytotaxa, 2018)
A new tiny species of Minidiscus, M. vodyanitskiyi, was found in the water column collected from the central part of the Sea of Azov. Its morphology was examined by scanning electron microscopy, described and illustrated. This centric diatom is characterized by: 1) small valve diameter of less than 10 µm; 2) one central fultoportula surrounded by two satellite pores located opposite each other; 3) one rimoportula located one areola away from the central fultoportula which internally appears similar to a slit surrounded by a plan elliptic rim oriented radially or slightly tangentially; 4) 4–6 (10) marginal fultoportulae that are equally spaced on a border between the valve surface and valve mantle; 5) three satellite pores that surround every marginal fultoportula, where a central satellite pore is directed towards the valve margin; 6) hexa- or heptagonal pattern of valve areolae; and 7) a hyaline conical flange connects the cingulum with the valve. The new species is compared with similar ones. A new term ‘polygonal areolae pattern’ is proposed instead of ‘eccentric pattern’. The term emphasizes that the pattern comprises concentric polygons formed by tangential areolae rows. Its qualitative characteristic, ‘polygonality’, has been described which allows more precise differentiation of the geometry of the valve pattern and describing areolae size variability.